Rhetoric and Educational Policies on the Use of History - Wong, Jessie Y. Y. (Education Policy Analysis Archives, 1997)
This article attempts to review the rhetoric and the educational policies on the use of history for citizenship education from 1880-1990 in England. In many instances, the rhetoric served as powerful tools to gain the support of educational authorities, namely, the Board of Education, Ministry of Education and Examination Boards. Their support was reflected in the change of educational policies and school syllabi that followed. This study shows that there was strong and consistent widespread rhetoric on history's contribution to citizenship education throughout the century, neither stopped by the two great wars nor impeded by the challenge of social studies as a citizenship subject after the Second World War. Instead it was challenged by the discipline itself in the early 1980s when some historians began to doubt the "new" history on the ground that the "real" history was being devalued. Consequently, there was evidence that the "new" history did not take off widely. In many schools, history was taught for its own sake. Its value for the education of modern citizenship was not being emphasised. This article ends with the argument that under the environment of the National Curriculum, first implemented in the country in 1989, history still claims its relevance for citizenship education.